Treatment Patterns and Burden of Illness in Patients Initiating Targeted Therapy or Chemotherapy for Pancreatic Neuroendocrine Tumors. Issue 7 (August 2017) - Broder, Michael S.; Chang, Eunice; Reddy, Sheila R.; Neary, Maureen P.
Abstract : Objective: The aim of this study was to characterize treatment patterns and burden of pancreatic neuroendocrine tumors (PNET). Methods: Using 2 claims databases, we identified patients with PNET initiating targeted therapy (everolimus, sunitinib) or chemotherapy from 2009 to 2012. The first targeted/cytotoxic therapy was considered index treatment. Treatment patterns were graphically evaluated from index treatment initiation until enrollment or study end, whichever occurred first. Disease burden was examined by index group for first follow-up year. Results: In treatment pattern analyses (582 newly treated patients with PNET), 72.2% received chemotherapy index treatment, 16.2% everolimus, and 11.7% received sunitinib. Median index treatment duration was 242, 146, and 126 days for everolimus, sunitinib, and cytotoxics ( P < 0.01). Sunitinib initiators switched most often followed by everolimus and cytotoxic initiators. In disease burden analyses, 338 patients met inclusion criteria, with mean age of 54.5 (standard deviation, 9.9) years, 45.6% were female, and there were no significant between-group differences. Targeted therapy initiators had more prior somatostatin analog use versus cytotoxics (53.4% vs 25.1%, P < 0.001); 72.5% had comorbidities after treatment initiation; 42.9% had 1 or more inpatient hospitalization; and 47.9% had 1 or more emergency department visit. Conclusions: Pancreatic neuroendocrine tumor treatment patterns varied; cytotoxics were more often used as early therapy than targeted agents, but for less time. Patients had high health care utilization, irrespective of treatment, potentially from burdensome symptoms and comorbidities.